1998
DOI: 10.1016/s0022-5347(01)62588-6
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Surgical Management of Bilateral Wilms Tumor: Results of the United Kingdom Children's Cancer Study Group

Abstract: Conservative surgical treatment of favorable histology bilateral Wilms tumor may improve the preservation of renal mass and function without impairing patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 18 publications
5
29
3
Order By: Relevance
“…In 1979, NWTS-3 formally recommended initial biopsy and chemotherapy before surgical resection of bilateral tumors [6]. Since that time, multiple studies have confirmed the beneficial effects of neo-adjuvant chemotherapy followed by conservative surgical resection in amenable, favorable histology BWT cases [7,8]. This demonstrates that pre-operative chemotherapy allows tumor shrinkage, leading to easier resection with preservation of unaffected parenchyma as well as decreased tumor spillage.…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, NWTS-3 formally recommended initial biopsy and chemotherapy before surgical resection of bilateral tumors [6]. Since that time, multiple studies have confirmed the beneficial effects of neo-adjuvant chemotherapy followed by conservative surgical resection in amenable, favorable histology BWT cases [7,8]. This demonstrates that pre-operative chemotherapy allows tumor shrinkage, leading to easier resection with preservation of unaffected parenchyma as well as decreased tumor spillage.…”
Section: Discussionmentioning
confidence: 99%
“…In the NWTS-4, 36 of 186 patients (19.4 %) with synchronous, bilateral Wilms tumors underwent bilateral nephron-sparing procedures [17]. Other smaller series have reported performing bilateral nephron-sparing procedures in from 30 to 70 % of patients with bilateral Wilms tumors [2,14,18]. Davidoff et al [19] reported on the feasibility and outcome of nephron sparing surgery (NSS) in ten children with bilateral Wilms tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of renal tissue is important to decrease the incidence of renal failure, which approaches 15 % at 15 years post-treatment in patients with bilateral Wilms tumor [3,4]. Currently unilateral Wilms tumor associated with predisposing syndromes are treated with a strategy that mirrors the approach followed for children with bilateral tumors or neoplasms arising in a solitary kidney [2][3][4]. However several centers, have also explored the role of Nephron-sparing procedures in children with unilateral non-syndromic Wilms tumors [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous protocols allowed for primary resection of tumours followed by chemotherapy. While the overall survival in a study by the United Kingdom Children's Cancer Study Group was similar in those undergoing primary surgery followed by chemotherapy and those treated with neoadjuvant chemotherapy followed by surgery, the incidence of renal failure was 20% in the initial surgery group versus 6% in the initial chemotherapy group (26).…”
Section: Managementmentioning
confidence: 94%